2015
DOI: 10.1016/j.marchem.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Annual study of oxygenated volatile organic compounds in UK shelf waters

Abstract: a b s t r a c tWe performed an annual study of oxygenated volatile organic compound (OVOC) seawater concentrations at a site off Plymouth, UK in the Western English Channel over the period of February 2011-March 2012. Acetone concentrations ranged from 2-10 nM (nanomole/L) in surface waters with a maximum observed in summer. Concentrations correlated positively with net shortwave radiation and UV light, suggestive of photochemically linked acetone production. We observed a clear decline in acetone concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 56 publications
(112 reference statements)
10
58
3
Order By: Relevance
“…There is evidence that the ocean can serve as a significant source of acetone to the atmosphere in certain regions and a significant sink in others [ Marandino et al ., ; Tanimoto et al ., ; Yang et al ., ; Zhou and Mopper , ]. Several very recent papers have increased our understanding of the ocean‐atmosphere exchange of acetone [ Beale et al ., , ; Dixon et al ., , ; Tanimoto et al ., ; Yang et al ., , ]. Enriched concentrations of acetone have been measured in the surface mixed layer [ Beale et al ., ] and surface microlayer [ Zhou and Mopper , ].…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that the ocean can serve as a significant source of acetone to the atmosphere in certain regions and a significant sink in others [ Marandino et al ., ; Tanimoto et al ., ; Yang et al ., ; Zhou and Mopper , ]. Several very recent papers have increased our understanding of the ocean‐atmosphere exchange of acetone [ Beale et al ., , ; Dixon et al ., , ; Tanimoto et al ., ; Yang et al ., , ]. Enriched concentrations of acetone have been measured in the surface mixed layer [ Beale et al ., ] and surface microlayer [ Zhou and Mopper , ].…”
Section: Methodsmentioning
confidence: 99%
“…Incubations of 10 nM (final concentration) 14 C-labelled methanol with surface seawater samples of 1 ml (methanol dissimilation to CO 2 ) and 320 ml 5 (methanol assimilation into biomass) were used to measure microbial utilisation rates. In situ surface methanol concentrations during the sampling period ranged between 34 and 68 nM (Beale et al 2015), thus our radioisotope additions represent between 15 and 29% of in situ concentrations. Incubations were conducted in triplicate at in situ temperatures and in the dark, together with negative controls 'killed' with 5% w/v trichloroacetic acid, TCA, (final 10 concentration), for dissimilation samples or 0.01% w/v mercuric chloride, HgCl 2 (final concentration) for assimilation samples (due to differences in sample volume).…”
Section: Microbial Methanol Utilisationmentioning
confidence: 95%
“…Recent direct flux measurements of methanol also demonstrated a consistent flux of methanol from the atmosphere to surface waters along a meridional transect of the remote Atlantic Ocean (Yang 15 et al 2013) and the Greenland Sea (Yang et al 2014b). Methanol is ubiquitous in atmospheric and marine environments where seawater concentrations have been reported ranging between <27 and 429 nM (Williams et al 2004, Kameyama et al 2010, Yang et al 2013, Yang et al 2014b, Beale et al 2015). An annual study in the western English Channel reported surface seawater methanol concentrations ranging between 16 and 20 78 nM over an annual cycle with no obvious seasonality (Beale et al 2015).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations